2004
DOI: 10.1046/j.1365-2036.2003.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of ciclosporin as therapy for autoimmune diseases of the liver in children and adolescents

Abstract: Summary Background : Conventional treatment for autoimmune hepatitis results in a significant percentage of failures and several, poorly tolerated, side‐effects. Therapy for autoimmune cholangitis and giant cell hepatitis associated with autoimmune haemolysis is poorly documented. Ciclosporin is a promising treatment for all of these diseases. Methods : We reviewed the records of 12 patients treated in our unit between 1987 and 2001. Eight had autoimmune hepatitis, two had autoimmune cholangitis and two had gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
0
28
1
2
Order By: Relevance
“…CSA was generally well tolerated, and no renal insufficiency occurred. In another retrospective review 12 patients were treated with CSA: 8 patients with AIH, 2 with autoimmune cholangitis and 2 with giant cell hepatitis [186]. CSA was used in 4 with treatment failure and in 8 who refused steroids or had steroid contraindications.…”
Section: Cyclosporinementioning
confidence: 99%
“…CSA was generally well tolerated, and no renal insufficiency occurred. In another retrospective review 12 patients were treated with CSA: 8 patients with AIH, 2 with autoimmune cholangitis and 2 with giant cell hepatitis [186]. CSA was used in 4 with treatment failure and in 8 who refused steroids or had steroid contraindications.…”
Section: Cyclosporinementioning
confidence: 99%
“…Cyclosporine seemed to be a promising answer. Cyclosporine has been used in pediatric (7)(8)(9)(10)(11) and adult (12)(13)(14) autoimmune hepatitis patients with reported success and good tolerability. Malekzadeh et al (12) reported on a series of adult autoimmune hepatitis patients treated with cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that cyclosporine may be effective in autoimmune hepatitis patients (7)(8)(9)(10)(11)(12)(13)(14). We present a case of successful cyclosporine use in a patient with autoimmune cirrhosis who was intolerant of azathioprine.…”
Section: Introductionmentioning
confidence: 92%
“…Patients who fail azathioprine therapy or with refractory relapsing disease should be considered for treatment with mycophenolate mofetil, which can lead to remission in approximately 10% of children [101]. Calcineurin inhibitors (cyclosporine and tacrolimus) have also been used with good efficacy, but the data is limited to small numbers and limited long-term follow-up [102][103][104][105]. -Disease relapse.…”
Section: Key Management Issuesmentioning
confidence: 99%